REFLECTIONS OF MADURESE LOCAL POLITICS IN THE SHORT STORY MATA CELURIT BY MUNA MASYARI: A GRAMSCIAN HEGEMONY ANALYSIS - Ruddin, Moh.; Oktaviani, Santi; Tabrani, Akhmad (Universitas Muhammadiyah Makassar, 2025)
Gramsci's hegemony study offers an innovative perspective on literature, which does not merely reflect class structures, but also has autonomous social, political and cultural dimensions. The short story Mata Celurit represents the local political reality of Madura, especially in the village head election, which is full of power struggles and cunning intrigues. This research is based on descriptive qualitative method, with the main object of Mata Celurit short story published on Kompas website. The unit of analysis used in this research refers to Gramsci's theory of hegemony, which is associated with the political phenomenon of Madurese society in the local democratic event, namely the election of kalebun (village head). The primary source of this research is the short story Mata Celurit, which is strengthened by secondary sources in the form of master books, journal articles, and relevant research. The researcher acts as a key instrument in the process of analysing the short story. The data collection technique is done through reading and note-taking, literature review, and data tabulation. Furthermore, the tabulated data was analysed in depth using the discourse analysis method. To ensure the validity of the data, researchers applied data triangulation techniques. Based on the results and discussion, it was found that ideological domination exercised by the political community to hegemonise civil society includes tyrannical power, material as a political instrument, covert threat actions, religious legitimacy, and political manipulation and intimidation. Meanwhile, the ideological domination of civil society includes opposing political dynasties and obedience to the ruling authority. Through the resulting discourse, Mata Celurit presents the phenomenon of percaton land as an issue that influences hegemony. Gramsci's analysis of hegemony reflects that the author not only presents a person (society), but also serves to reveal the hegemony exercised in political contestation in the village in Madurese society. This research can be an inspiration for the community, academics, and writers to be more sensitive to hegemonic practices that occur in the surrounding environment, especially in the context of village politics in Madura. Mata Celurit short story can be used as a critical literacy media to increase public awareness about the importance of understanding and criticising the domination of power.